2019
DOI: 10.1021/acs.jpcc.8b12030
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Long-Term Storage for Fluorine-Substituted Aromatic Self-Assembled Monolayers by the Example of 4-Fluorobenzene-1-Thiolate Films on Au(111)

Abstract: By the example of 4-fluorobenzene-1-thiolate (p-FTP) films on Au(111), we show that a long-term postpreparation storage can improve significantly the quality of fluorinated aromatic self-assembled monolayers (SAMs). Whereas the freshly prepared p-FTP films exhibit a polymorphism, with a dominance of a disordered phase, the postpreparation storage triggers a gradual phase transition to a single-phase SAM of exceptional quality. This phase is characterized by the commensurate (16 × √3) structure, a molecular foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
2
6
0
1
Order By: Relevance
“…The 4-fluorobenzene-1-thiolate molecular layer showed a main C­(1s) peak at 284.3 eV as well as a smaller high binding-energy peak at 286.3 eV in Figure b. The binding energies and relative intensities observed for the 4-fluorobenzene-1-thiolate molecular layer on nanoporous gold were consistent with previous measurements of the molecule attached to planar gold surfaces, in which the peak at 284.3 eV was attributed to the nonfluorine-substituted atoms of the phenyl ring and the peak at 286.3 eV was attributed to the carbon atom directly bonded to the fluorine atom. , We did not observe a significant π–π* peak for the molecular layers. Analysis of the S­(2p) region, included in Figure S2, shows the expected peak at 162.0 eV from sulfur chemisorbed on the gold surface with a thiolate bond.…”
Section: Results and Discussionsupporting
confidence: 88%
“…The 4-fluorobenzene-1-thiolate molecular layer showed a main C­(1s) peak at 284.3 eV as well as a smaller high binding-energy peak at 286.3 eV in Figure b. The binding energies and relative intensities observed for the 4-fluorobenzene-1-thiolate molecular layer on nanoporous gold were consistent with previous measurements of the molecule attached to planar gold surfaces, in which the peak at 284.3 eV was attributed to the nonfluorine-substituted atoms of the phenyl ring and the peak at 286.3 eV was attributed to the carbon atom directly bonded to the fluorine atom. , We did not observe a significant π–π* peak for the molecular layers. Analysis of the S­(2p) region, included in Figure S2, shows the expected peak at 162.0 eV from sulfur chemisorbed on the gold surface with a thiolate bond.…”
Section: Results and Discussionsupporting
confidence: 88%
“…Another interesting feature of vacancy islands is that they often have a long straight-edge structure in the same direction near ordered rows, as indicated by the white dotted lines, although vacancy islands with round or triangular shapes were usually observed for alkanethiol or aromatic thiol SAMs. 1,4,7,9,17,19,42,52,75 Similar results showing straight-edge structures of vacancy islands were also observed for methaneselenolate (C1Se) or dodecaneselenolate (C12Se) SAMs on Au(111) derived from the corresponding dialkyl diselenides at elevated deposition temperatures as well as for benzeneselenolate SAMs derived from diphenyl diselenide. 50,52,54 These unique features of vacancy islands appeared at elevated temperatures and could indicate an intrinsic characteristic of selenolate SAMs resulting from the synergistic effect of the high mobility of gold−selenolate complexes 50 and strong collective van der Waals interactions between alkyl chains in the ordered rows (indicated by dotted lines).…”
Section: ■ Results and Discussionsupporting
confidence: 69%
“…In recent decades, self-assembled monolayers (SAMs) have drawn considerable attention because of their ease of preparation, high degree of structural order, superior reproducibility, high chemical stability, and functional tunability. Therefore, SAMs have been successfully applied to many technological applications in corrosion inhibition, , biointerfaces, ,, nanopatterns, , molecular electronics, , and organic thin-film transistors. , Two-dimensional (2D) or three-dimensional (3D) molecular arrangements of SAMs at the molecular level can readily be controlled by changing chemical interactions between the headgroup of the molecule and the substrate and van der Waals interactions between molecular backbones, which significantly affect the physical and chemical properties of SAM-based application systems. ,, Previous work showed that charge-transport characteristics and stability of electronic devices are highly dependent on SAM constituents and their adsorption geometries. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, taking into account the results of ref [8h] (see above) and our experience with the analogous systems, [8i,k] we used a large tip‐sample separation distance with a tunneling impedance of ∼6.00 GΩ (a tunneling current of 0.10 nA and a sample bias of 0.60 V) to ensure that the STM tip neither penetrated into the SAMs nor imposed any damage of the monolayers. The above choice of the parameters was strongly affected by the fact that the measurements were performed under the ambient conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This is particular of importance for short, one‐ring aromatic molecules, which are particularly relevant for engineering of interfaces in organic electronics and photovoltaics in view of their higher electrical conductance compared to the molecules with longer aromatic backbone [9] . It was found that the structural ordering in the respective SAMs relies strongly on the preparation conditions, such as the immersion time (IT), [8h,j,k] temperature [2a,8b,e,h] and long‐term storage [8i] . For instance, it was reported that the SAMs formed by pentafluorobenzenethiol (PFBT) on Au(111) substrates at low temperatures contain numerous structural defects, such as disordered phases, dislocations of molecular rows, and variation of apparent topographical height in these rows [8b,e,h] .…”
Section: Introductionmentioning
confidence: 99%